Investigating the addition of enzymes in gluten-free flours - The effect on pasting and textural properties - Palabiyik, Ibrahim; Yildiz, Onder; Toker, Omer Said; Cavus, Mustafa; Ceylan, Mehmet Murat; Yurt, Bayram (ELSEVIER SCIENCE BV, 2016)
A wide range of enzymes (fungal amylase, esterase, hemicellulase, glucose oxidase and transglutaminase) were added to gluten-free flours (buckwheat, corn and rice) at different concentrations (0, 1, 3, 5,10 g/100 kg flour) to investigate the effects on pasting properties of flour and texture profiles of the flour gels. Concerning the pasting properties, fungal amylase enzyme consistently affected the flour properties. Breakdown of complex starch molecules into simpler sugars due to the enzyme activity decreased the overall viscosity parameters (at least trough viscosity by 50%, breakdown viscosity by 80%, final viscosity by 60% and setback viscosity by 67%) during the application of heating, shearing and cooling cycle. Increasing enzyme concentration decreased these values further due to increase in the rate of hydrolysis. Texture profiles of the flour gels showed good relation with pasting properties. Decreasing viscosity of gluten-free gels by enzymes caused reduction in the firmness of the gels. The hardest gel was found as corn flour at the highest amylase enzyme concentration (10 g/100 kg flour). However, the highest springiness, resilience, cohesiveness and adhesiveness value was observed for buckwheat starch gel. (C) 2016 Published by Elsevier Ltd.
Keywords: Gel; Additive; Starch; Pasting property; Texture; FREE BREAD; RICE FLOUR; MICROBIAL TRANSGLUTAMINASE; RHEOLOGICAL PROPERTIES; WHEAT CULTIVARS; TAPIOCA STARCH; BREADMAKING; QUALITY; DOUGH; HYDROCOLLOIDS; Food Science & Technology